Research on the propagation of laser beams array with coherent and incoherent combination in dynamic atmosphere turbulence - Deng, Wantao; Wang, Chengcheng; Gan, Chunquan; Xue, Liangping; Xia, Huijun; Wang, Peng; Yang, Huan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
High-power laser systems mostly use coherent or incoherent combined beams to achieve higher laser output power to satisfy the application. However, the far-field beam quality of laser will be reduced when propagating over atmosphere. Based on the propagation model of laser beams array, we use atmospheric coherence length, laser duration and average wind velocity to construct dynamic atmospheric turbulence which is characterized as a phase screen sequence. Meanwhile, considered as the indexes to evaluate beam quality, peak intensity and intensity in bucket are comparatively analysed in coherent and incoherent combined beams in far-field. The results indicate that in weaker turbulence circumstances, coherent combined beam has an advantage compared with the incoherent combined beams when laser duration is short, and coherent combination is more suitable for pulsed laser. With laser duration is increasing, the beam quality of incoherent and coherent combined beams both decrease and tend to be close. In stronger turbulence circumstances, the corresponding laser duration will be shorter when the beam quality of coherent combined beams is extraordinary close to that of incoherent combined beams. The researches can provide important data for high-power laser system to select the optimal beam combination mode to improve its performance.
Optica Applicata, Vol. 52, 2022, nr 2, s. 243-257
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; laser propagation; dynamic atmospheric turbulence; coherent combination; incoherent combination; beam quality